Accelerating cine-MR imaging in mouse hearts using compressed sensing. - Wech, T; Lemke, A; Medway, D; Stork, L; Lygate, C; Neubauer, S; Köstler, H; Schneider, J (2011)
PURPOSE: To combine global cardiac function imaging with compressed sensing (CS) in order to reduce scan time and to validate this technique in normal mouse hearts and in a murine model of chronic myocardial infarction. MATERIALS AND METHODS: To determine the maximally achievable acceleration factor, fully acquired cine data, obtained in sham and chronically infarcted (MI) mouse hearts were 2-4-fold undersampled retrospectively, followed by CS reconstruction and blinded image segmentation. Subsequently, dedicated CS sampling schemes were implemented at a preclinical 9.4 T magnetic resonance imaging (MRI) system, and 2- and 3-fold undersampled cine data were acquired in normal mouse hearts with high temporal and spatial resolution. RESULTS: The retrospective analysis demonstrated that an undersampling factor of three is feasible without impairing accuracy of cardiac functional parameters. Dedicated CS sampling schemes applied prospectively to normal mouse hearts yielded comparable left-ventricular functional parameters, and intra- and interobserver variability between fully and 3-fold undersampled data. CONCLUSION: This study introduces and validates an alternative means to speed up experimental cine-MRI without the need for expensive hardware.